1990
DOI: 10.1063/1.346574
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals epitaxial growth and characterization of MoSe2 thin films on SnS2

Abstract: A variation on molecular beam epitaxy (MBE), called van der Waals epitaxy, is described where a material with primarily two-dimensional (2D) bonding is grown on a substrate which also has a 2D structure. Lattice matching difficulties, which limit the choice of materials in MBE of 3D systems, are circumvented since the interlayer bonding is from weak van der Waals interactions. The title system shows a lattice mismatch of 10% yet high quality epitaxial films can be grown. The films were characterized in situ wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 10 publications
12
97
0
Order By: Relevance
“…azimuthially aligned (Fig. 1), suggesting that the epilayers are epitaxially grown such that [11][12][13][14][15][16][17][18][19][20] 6,7,16 indicating the absence of strain as would be expected in van der Waals heteroepitaxy 17,18 of these materials.…”
mentioning
confidence: 99%
“…azimuthially aligned (Fig. 1), suggesting that the epilayers are epitaxially grown such that [11][12][13][14][15][16][17][18][19][20] 6,7,16 indicating the absence of strain as would be expected in van der Waals heteroepitaxy 17,18 of these materials.…”
mentioning
confidence: 99%
“…This goes farther than the observation made by Ohuchi et al, when van der Waals epitaxy on the sulfurterminated GaAs surface was first demonstrated: ''...inertness of the surfaces as well as absence of surface dangling bonds appear to be prerequisites of the ͓van der Waals epitaxy͔ process.'' 4 We find that van der Waals epitaxy is possible if the film has a layered structure and the substrate is well ordered ͑but not necessarily also of a layered structure͒.…”
Section: Discussionmentioning
confidence: 99%
“…For TEM examination, the cross-sectional samples were prepared first by mechanical thinning and then argon ion milling; images were obtained using 200 kV Jeol 2000 EX and Topcon EM002B electron microscopes. 4 He ϩ backscattering measurements ͑for compositional characterization and thickness estimation͒ and channeling measurements ͑for characterizing the crystallographic alignment͒ were made using a scattering angle of 170°. When an optimal mass resolution was desired ͑hence separating the gallium and selenium signals for thin films͒, an incoming beam energy of 3.1 MeV was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the base of MBE, so-called van der Waals epitaxy was achieved in the 1980s [104][105][106][107]. van der Waals epitaxy is realizable for the materials with layered structure, such as graphene and TMDs, where the layers are weakly bound by van der Waals forces.…”
Section: Preparation Techniquesmentioning
confidence: 99%